Legal Analysis of the Implementation Process of Simultaneous Village Head Elections In East Lombok Based on The Stipulations of Law Number 6 of 2014 - Ihsan, Khaerul; Jiwantara, Firzhal Arzhi; Hasanah, Siti (Faculty of Law, Universitas Pekalongan, 2024)
Based on the terms of Act No. 6 of 2014 on the village, this study focuses at the implementation stage of the election of a village chief in the eastern Lombok district. The purpose of this study is to examine the legal processes that must be followed in order to choose a village chief and how these rules are actually implemented in the field. This research combines literary studies, legislative-legislative techniques, and normative jurisprudential procedures. The study's findings demonstrated that the East Lombok district's simultaneous head of village election has been conducted in accordance with the procedures outlined in Act No. 6 of 2014, which include the stages of preparation, candidate registration, campaigning, voting, tabulating votes, and determining the election's outcome. Nonetheless, there are several implementation roadblocks that must be overcome, like the public's poor socialisation of legislation and technical issues with the voting procedure. In order to make future improvements to the village chief election system, this article recommends increased socialisation, training for the election committee, and continuous evaluation.